Fractionation and Speciation of Arsenic in Agricultural Soils in West Bengal, India - Sinha, B.; Bhattacharyya, K. (International Journal of Bio-resource and Stress Management, 2017)
Arsenic a toxic trace metalloid is of great environmental concern due to its presence in soil, water, plant and human continuum. Its high toxicity and increased appearance in biosphere has triggered public and political concern. Widespread arsenic (As) contamination in West Bengal, India is of great concern as it affects millions of people due to its toxicity. Arsenic in ground water, soil present as dissolved oxyanions namely arsenate and arsenite.Groundwater, when used for irrigation, helps entry of arsenic into the food chain via a soil-plant-animal continuum. In this study the extent of geo accumulation is measured in order to assess the degree of arsenic contamination in soil. A sequential fractionation study of arsenic revealed that out of all the fractions, the Fe/Mn bound arsenic has emerged to be most predominant fraction in all the experimental soils, sharing 38.2 to 73.3% of total soil arsenic recovered from the soils under study while the least proportions were retrieved from water soluble fractions. The variation in fractions may be attributed to the mineralogical make-up of soils along with some physicochemical factors. Arsenic speciation study showed that As-V appeared to be the major species while As (III) was found at a minor concentration.. The extraction efficiency of the selected reagent was observed to be substantially low in a number of soils as the majority of As is strongly bonded to Fe, Al and Mn particles of the soil.